2013
DOI: 10.1016/j.ultsonch.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on different quality parameters of apple juice

Abstract: Fresh apple juice treated with ultrasound (for 0, 30, 60 and 90 min, at 20 °C, 25 kHz frequency) was evaluated for different physico-chemical, Hunter color values, cloud value, antioxidant capacity, scavenging activity on 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical, ascorbic acid, total phenolics, flavonoids, flavonols and microbial characteristics. No significant effect of sonication was observed on pH, total soluble solids (°Brix) and titratable acidity of apple juice. Sonication significantly improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
223
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(281 citation statements)
references
References 22 publications
49
223
3
2
Order By: Relevance
“…As shown in Table 3, results showed a remarkable (p < 0.05) enhancement in polyphenol and anthocyanidin of blueberry juice treated with sonication for 40 min as compared with juices sonicated for 20 min and the control. Abid et al (2013) observed the identical result that sonication could enhance total phenols of apple juice. These experimental results revealed that sonication enhanced bioactive compounds content in the juice.…”
Section: Impact Of Sonication On Total Sugars Soluble Solids Polyphmentioning
confidence: 65%
See 2 more Smart Citations
“…As shown in Table 3, results showed a remarkable (p < 0.05) enhancement in polyphenol and anthocyanidin of blueberry juice treated with sonication for 40 min as compared with juices sonicated for 20 min and the control. Abid et al (2013) observed the identical result that sonication could enhance total phenols of apple juice. These experimental results revealed that sonication enhanced bioactive compounds content in the juice.…”
Section: Impact Of Sonication On Total Sugars Soluble Solids Polyphmentioning
confidence: 65%
“…The increase in radicals scavenging activity was possibly ascribed to the enhancement in polyphenolic compounds and anthocyanins in blueberry juice during sonication (Abid et al, 2013). The longer sonication time was, the more antioxidants could enter solution and the more free radicals could be scavenged.…”
Section: Impact Of Sonication On Radical Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial analysis of control and treated juice samples were performed by the method previously reported by Abid et al (2013) with a minor modification. Total plate count was determined by pour plate method.…”
Section: Microbial Analysismentioning
confidence: 99%
“…In recent studies about effect of sonication on apple juice (Abid et al, 2013), kasturi lime juice (Bhat et al, 2011), cantaloupe melon juice (Fonteles et al, 2012) and orange juice (Tiwari et al, 2008), ultrasound treatment technology has been proved to a desirable method of juice processing, which can avoid losses in beneficial nutrients and reduce the microbial load in the fruit juices. It is considered to be more advantageous due to its shortened processing time with lower energy consumption (Abid et al, 2014).…”
Section: Introductionmentioning
confidence: 99%